Issues in the Planning of a Multilingual Explanatory Dictionary of Chemistry for South African Students - Carstens, Adelia (Lexikos, 1997)
Developing human potential and actively promoting science and technology are among the priorities of the present South African government. Significant progress in these areas can only be made if relevant education and training are provided timeously. Surveys conducted by overseas as well as local researchers indicate that mother-tongue education is one of the measures to improve learning. While mother-tongue education at secondary and tertiary level is at present not provided to speakers of African languages, compromise solutions have to be offered, such as multilingual explanatory special-field dictionaries. By providing linguistic and encyclopedic information in English, Afrikaans and two or more of the African languages the concepts of the subject-field are made accessible via the language(s) of wider communication as well as via the mother tongue of the student. Although there are many difficulties and potential pitfalls awaiting terminographers and special-field experts who attempt a project of this nature, substantial preliminary work that has already been done with regard to a quadrilingual explanatory dictionary of chemistry indicated that this ideal is not out of reach. The compilers believe that successful completion of the project, as well as favourable results, will verify the hypotheses that served as points of departure for the project.